Approaching the Unfamiliar: How the Religious Ways of Aboriginal Peoples Are Understood in Delgamuukw v. British Columbia (1997) - Forbes, Lauren L. (Université d'Ottawa / University of Ottawa, 2012)
This thesis will explore how the Supreme Court of Canada understands and frames the religious ways of the Gitksan and Wet’suwet’en First Nations peoples, in the case Delgamuukw v. British Columbia (1997). The case started as a land claims case but at the Supreme Court level it became about whether Aboriginal oral knowledge could be used as historical evidence in a Canadian court of law, in particular for this dispute, as an aid for First Nations peoples to establish title to their traditional territories. The Court decided that Aboriginal oral knowledge could be used as evidence. This thesis does five things: 1. It examines some of the tools that can be used to examine and evaluate how the religious ways of Aboriginal peoples are discussed in law in Canada. Here it focuses on using a broad understanding of religion as “lived” to understand religion. It also establishes a social-scientific method of discourse analysis, drawn from a number of sources, to evaluate legal documents. 2. This thesis explores the socio-legal context in Canada in which Aboriginal peoples and their claims need to be understood. Here the presence of European and Christian views that are still present in society and social institutions in Canada and the way they affect how Aboriginal religious ways are understood is determined. The characteristics of law that make it difficult for Aboriginal claims to be understood and handled adequately in court in Canada are also investigated. 3. The third aspect that this thesis focuses on the markers of the religious ways of Aboriginal peoples in the Delgamuukw case and how are they understood in the Canadian socio-legal context. Here there is discussion of oral knowledge, land, crests, feasting and totem poles and what each might mean for the Gitksan and Wet’suwet’en peoples and how the legal system might have trouble handling them. 4. Analysis of the Delgamuukw case is the fourth part of this thesis. How the law understands and frames the religious ways of the Gitksan and Wet’suwet’en peoples in the Delgamuukw case are investigated. It is determined that the Court downplayed the religious ways of Aboriginal peoples (by “writing out”, by using vague language to refer to it or by not mentioning it at all); it did not do justice to Aboriginal beliefs by labeling oral knowledge as “sacred”; the Delgamuukw decision fell short of really treating oral knowledge as equal to other forms of historical evidence by excluding oral knowledge with religious content; legal adjudicators made pronouncements on the religious uses of land for the Gitksan and Wet’suwet’en and finally; land was quantified, regulated and title was diminished by the ability for the court to infringe on it. What these actions by the Court suggested about how it understands religion and the religious ways of Aboriginal peoples where also contemplated. It was noted that the law characterized issues and used language in particular ways to avoid discussing religion, to discount it as evidence, and used a Christian understanding of religion to comprehend Aboriginal religious ways, which did not do justice to their beliefs. 5. The last part of this thesis questions whether there other ways in which the law, and the majority of non-Aboriginal peoples in Canada, could come to better understand and handle the religious ways of Aboriginal peoples than they did in the Delgamuukw case. It determines that there are a number of indications that suggest that this is possible including, the unique historical situation of Canada, the teaching and communication skills present in many Aboriginal communities, the space opened surrounding the inclusion of oral knowledge as evidence in law, increasing dialogue with Aboriginal communities, and the current revaluation of history. Nevertheless, there is also an ambivalence on behalf of the law regarding whether or not it will go in the direction that could view Aboriginal religious ways in alternative ways which could result in a better understanding these ways on their own terms. The thesis concludes that according to analysis of the Delgamuukw case, law has difficulty understanding and handling the religious ways of Aboriginal peoples in Canada.
Keywords: Religion; Spirituality; First Nations; Oral History; Land Claim; Religious Ways; Aboriginal Peoples; Canada; Delgamuukw v. British Columbia (1997); Supreme Court; Gitksan; Wet'suwet'en; Delgamuukw